Raman gains of ADP and KDP crystals - 周海亮 张清华 王波 许心光 王正平 孙洵 张芳 张立松 刘宝安 柴向旭 (Chinese physics B, 2015)
In this paper, the Raman gain coefficients of ammonium dihydrogen phosphate （ADP） and potassium dihydrogen phosphate （KDP） crystals are measured. By using a pump source of a 30-ps, 532-nm laser, the gain coefficients of ADP and KDP are 1.22 cm/GW, and 0.91 cm/GW, respectively. While for a 20-ps, 355-nm pump laser, the gain coefficients of these two crystals are similar, which are 1.95 cm/GW for ADP and 1.86 for KDP. The present results indicate that for ultra-violet frequency conversion, the problem of stimulated Raman scattering for ADP crystal will not be more serious than that for KDP crystal. Considering other advantages such the larger nonlinear optical coefficient, higher laser damage threshold, and lower noncritical phase-matching temperature, it can be anticipated that ADP will be a powerful competitor to KDP in large aperture, high energy third-harmonic generation or fourth-harmonic generation applications.